Gender differences in tuberculosis incidence rates—A pooled analysis of data from seven high-income countries by age group and time period - Peer, Victoria; Schwartz, Naama; Green, Manfred S. (Frontiers in Public Health, 2023)
Introduction Gender differences in the incidence rates for tuberculosis are occasionally reported. However, the magnitude and consistency of the differences by age group, among different populations, and over extended periods of time are not clear. Materials and methods We obtained national data from seven countries from open-access internet sites or personal communications with official representatives. We computed the male-to-female incidence rate ratios (IRRs) by country and year for every age group and pooled these ratios using meta-analytic methods. Meta-regression analysis was performed to estimate the contribution of age, country, and calendar years to the variation in the IRRs. Results In the age groups of < 1, 1–4, 5–9, and 10–14, the pooled male-to-female IRRs (with 95% CI) were as follows: 1.21 (1.05, 1.40), 0.99 (0.95, 1.04), 1.01 (0.96, 1.06), and 0.83 (0.77, 0.89), respectively. In the age groups 15–44, 45–64, and 65+ years, incidence rates were significantly higher in men, with IRRs of 1.25 (1.16, 1.35), 1.79 (1.56, 2.06), and 1.81 (1.66, 1.96), respectively. Meta-regression analysis revealed that age significantly contributed to the variation in the IRRs. Conclusions There were gender differences in the incidence rates for tuberculosis, with higher rates in boys aged less than one, no significant differences in boys of ages 1–9, and higher rates in boys/men older than 15. The only excess in female gender was in the age group 10–14 years. The age-related gender differences in tuberculosis incidence rates observed over several countries indicate the importance of including sex as a biological variable when assessing the risk factors for tuberculosis.